Antifungal Activity of Endophytic Bacteria Isolated from Miana Plants (Coleus scutellarioides (L.) Benth.) against Candida albicans - Melda Yunita; Ruth Magdalena Lumbantobing; Ritha Tahitu (Folia Medica Indonesiana, 2023)
Highlights: